2022
DOI: 10.5751/es-13097-270203
|View full text |Cite
|
Sign up to set email alerts
|

Do all roads lead to Sapporo? The role of linking and bridging ties in evacuation decisions

Abstract: Why do some communities evacuate long-distances in higher rates than others after disaster? This mixed-methods study uses a new dataset of long-distance evacuation rates after Hokkaido's Eastern Iburi Earthquake in September 2018, aggregated to the city level from geolocated Facebook user movement. We found that communities with stronger linking and bridging social capital tended to see much lower evacuation rates to distant towns. We used statistical models, fieldwork, and content analysis of 12 interviews, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Gehlot et al (2019) found that residents with wider social networks traveled further when evacuating. Similarly, past studies of Facebook-related evacuation data found that individuals with stronger bridging and linking ties evacuate more (Fraser et al, 2020; Metaxa-Kakavouli et al, 2018).…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…Gehlot et al (2019) found that residents with wider social networks traveled further when evacuating. Similarly, past studies of Facebook-related evacuation data found that individuals with stronger bridging and linking ties evacuate more (Fraser et al, 2020; Metaxa-Kakavouli et al, 2018).…”
Section: Discussionsupporting
confidence: 55%
“…While not an all-encompassing measure of social vulnerability, wealth reflects a major social barrier for evacuation. Finally, to represent social capital, I use new Social Capital Indices for Japanese municipalities from 2017 (Fraser et al, 2022) and new social capital indices for US county subdivisions from 2018 (Fraser, Page-Tan, et al, 2022), based on Kyne and Aldrich’s (2020) Social Capital Indices for US counties. Third, the US and Japanese indices have demonstrated considerable external validity, consistently showing the same associations with key disaster outcomes as expected by literature, even in different national contexts (e.g., Fraser, 2021; Fraser, Cunningham, et al, 2021; Fraser, Page-Tan, et al, 2022; Kyne & Aldrich 2020).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations